Crataegus Oxyacantha Based on Bioinformatics Studies and Toxicity Test on The Chicken Embryo - Maslichah Mafruchati (JURNAL RISET RUMPUN ILMU HEWANI, 2025)
Hawthorn extract has been used for ameliorating cardiac disorders and pulmonary hypertension. The main chemical constituents of hawthorn flavonoid extract (HFE) include flavonoids (1-2%), oligomeric proanthocyanidins (1-3%), and other bioactive components (e.g., triterpene acids, organic acids, sterols, and cardioactive amines). These compounds are reported to have many pharmacological effects, including neuroprotective, hepatoprotective, cardioprotective, and nephroprotective effects. This study was aimed the analysis Crataegus oxyacantha based on a bioinformatic study and toxicity test on the chicken embryo. This method consisted of analysis of the three-dimensional structure of Crataegus oxyacantha Protein, Epitope and Allergen Proteins, Crataegus oxyacantha Proteins that were antigens and toxins and toxicity test on the chicken embryo. The results of research conducted on 3 three-dimensional structures of Crataegus oxyacantha protein, GQME value and QmeanDisCo value. In addition, this study also obtained the results of proteins that are epitope, antigenic, non-allergenic and non-toxic and toxicity test on the chicken embryo was 250 ng/egg..Morphological description of the embryo on the 21st day after injection, at a concentration of 250 ng of Crataegus oxyacantha /egg product, an abnormal embryological picture was obtained. Chicken Embryo Weight and Body Length Measurements were carried out in chicken embryos. Need research for other species of plant.